Optimizing Cucumber (Cucumis sativus L.) Fruit Metabolomics Under Elevated CO2 and High-Temperature Stress in the Greenhouse - Xian Du; Yang Song; Lu Pan; Shimao Cui (Horticulturae)
Elevated carbon dioxide concentrations can mitigate the significant threats of high-temperature stress to the yield and quality of cucumber fruit during summer. This study aims to elucidate the response mechanisms of cucumber fruit metabolomics under elevated CO2 and high-temperature stress while also exploring the potential benefits of elevated CO2 in mitigating the adverse effects of high temperatures. The fruits of the experimental material cucumber (Cucumis sativus L., ’Jinyou 35’) were grown under soil conditions in the greenhouse. We used untargeted metabolomics methods to analyze the effects of varying temperatures (normal temperatures of 25 to 35 °C and high temperatures of 35 to 45 °C) and CO2 concentrations (400 ± 20 µmol/mol and 1200 ± 20 µmol/mol) on the morpho-physiological traits, yield-associated traits, and metabolomic profiles of cucumber fruits. The results showed that, under high-temperature stress, elevated carbon dioxide concentrations altered 27 differential metabolites, including tyramine, xylitol, linolenic acid, L-asparagine, α-linolenic acid, and L-phenylalanine. These alterations are associated with the metabolic pathways of alanine, aspartate, glutamate, glutathione, glyoxylate, and dicarboxylic acids. Compared to adding carbon dioxide at normal temperatures, elevated carbon dioxide at high temperatures modified 38 differential metabolites, including vitamin B6, L-citrulline, inositol, L-aspartic acid, sucrose, and palmitic acid. These modifications were linked to the galactose metabolic pathway and the zeatin and arginine biosynthetic pathways. The accumulation of cysteine, glutamic acid, and glycine is essential to form the antioxidant glutathione; thus, cucumber fruits with a higher amino acid content exhibit an enhanced capacity to withstand severe high-temperature stress. Under high-temperature conditions, elevated carbon dioxide adds complexity to changes in differential metabolites within cucumber fruits. These fruits accumulate sugars, organic acids, and amino acids through the galactose metabolism pathway (map00052), the arginine biosynthesis pathway (map00220), and the glutamate synthesis pathway (map00250), thereby improving their heat resistance.